Supremely successful selling : discovering the magic ingredient - Panas, Jerold (Hoboken, N. J. : Wiley, 2012)
The guide to listening, building trust, and selling what the buyer wants Everyone sells--in every aspect of your life and no matter what your profession. Supremely Successful Selling describes the art of selling that helps the buyer understand the value and appeal of a product for their personal life or for their business. Replete with stories of some of the greatest sales people in the country, this book teaches you how to listen more than talk, become an ethical ambassador for your product, and understand that everything in life is selling. You'll learn how to take the fear out of asking, the ten actions to avoid, and the most powerful incentives that sell your product. Offers proven advice on how to get the appointment Shares the'Three Magic Questions' that engage a prospect Explains how to overcome objections, the power of the'Magic 7 Minutes,' and the Four Es that make a great Sales person Jerold Panas is one of the nation's leading consultants and a platform personality of note. He is the author of thirteen bestselling books and manages one of the largest consulting firms in the world for advising organizations and foundations on philanthropy. Let Jerry teach you how to ask questions, listen, build trust, and get to a'Yes.'
Contents note continued: ch. 19 Climb the Ladder of Success One Objection at a Time -- ch. 20 Objections Aren't Bitter if You Don't Swallow Them -- ch. 21 No Isn't an Answer, It's a Question -- ch. 22 The Horrifying 10 -- ch. 23 Have Only Two Dials on Your Console---Fast and Faster -- ch. 24 Integrity Isn't Important---It Is Everything -- ch. 25 Flimflam Is Out -- ch. 26 The Highest of Callings -- ch. 27 The Unconquerable Joy of Selling That Ignites a Fire -- ch. 28 You Don't Have to Be Great to Start, But You Have to Start to Be Great -- ch. 29 Here's the Magic.
Includes index.
Keywords: Selling; Integrity